노인의 체육활동 참여 실태 및 활성화 방안 연구 - 김양례; Yang Rea Kim; 구해모; Hai Mo Gu; 조성식; Seong Sik Cho (Ch'eyuk kwahak yŏn'gu, 2004)
본 연구는 만 60세 이상 노인의 체육활동 참여 실태를 분석하고 이를 토대로 노인체육진흥을 위한 활성화 방안을 제시하는데 목적이 있다. 연구대상은 2003년 현재 만 60세 이상의 노인을 모집단으로 설정한 다음 노인의 연령, 성, 거주지역 등을 고려하여 전국적으로 1,017명을 표집하였다. 본 연구의 대상을 만 60세 이상으로 선정한 이유는 노인복지법상 노인인 65세의 전 단계로서 노인체육의 주요 대상이 되기 때문이다. 조사도구로는 설문지가 사용되었다. 설문조사 문항은 문화관광부(2000)의 국민생활체육활동 참여 실태조사와 한국보건사회연구원(1998)의 전국 노인생활실태 및 복지욕구조사를 토대로 하였으며, 면접조사는 노인체육 전문가와 심층면접 등을 통해 초안을 작성한 후 보완 수정하여 완성한 후 사용하였다. 자료처리는 SPSS/PC+WINDOW VERSION10.0의 기존 프로그램을 활용하여 빈도분석과 χ2 검증을 실시하였다. 이러한 절차를 통해 노인의 체육활동 참여 현황과 체육활동 효과, 장애요인 등을 종합적으로 분석하고 이를 토대로 노인체육 활성화 방안을 인식제고, 제도, 프로그램, 지도자, 시설, 홍보 측면에서 제시하였다. 인식제고 측면에서는 노인이 인식하고 있는 주관적 참여 장애요인을 제고하기 위한 교육이, 제도적 측면에서는 공공체육시설에 경로우대 제도 도입과 공공체육시설 생활체육관 내 운동처방실 운영이 필요하다. 프로그램 측면에서는 노인체육 프로그램 확대 실시와 단체 스포츠종목 위주의 가족단위 체육활동 프로그램 확대가, 지도자 측면에서는 노인체육 전문 지도자 양성 및 배치가, 시설 측면에서는 시설 이용 극대화 및 복합 체육시설 건립이, 그리고 홍보 측면에서는 참여 촉진을 위한 홍보활동 강화가 필요하다. The purpose of this study was to examine the current status of physical activity of the aged and to propose the plans for improving sport participation for them. Total 1,017 subjects were samples from the population of over 60 years old aged considering at their age, sex, and residence area. The reason for this was that they were in preliminary stage of 65 years old which was prescribed as the aged in the elderly welfare act in Korea, and they were also the main targets for improving the elderly sport participation. For methodology, the survey method were used. The contents of the questionnaire were initially referred to previous works of Korea Ministry of Culture and Tourism(2000) and Korea Institute for Health and Social Affairs(1998). While the interview items were at first drafted by in-depth interviewing with the experts at these areas, and finally used after adequate supplements and revisions. The frequency analysis and chi-square test were performed using SPSS package for PC Windows. Throughout these procedures, the current status of physical activity of the aged, its effects, and barriers were analysed synthetically. And based upon the results, the plans for improving sport participation of the aged were proposed as being follows. ① From the side of raising recognition, the educational programs for promoting their recognition and removing the subjective and emotional barriers for the elderly to participate at physical activity should be set up. ② From the side of system, introducing preferential treatment of the elderly in the public physical activity facility, reenforcing the evaluation procedures of program development and introducing program certification system, and expanding supports at sports goods and managing them continuously were needed. ③ From the side of program, managing the physical activity prescription room in the public physical training gymnasia, developing and propagating specialized and tailor-made programs for elderly, and enlarging the family-oriented physical activity enterprises mainly as team sport events were needed. ④ From the side of instruction, training and arranging many professional instructors suitable for the various needs of the elderly were needed. ⑤ From the side of facility, both making full use of existing physical activity facility and erecting new sports complex were needed. ⑥ From the side of public relation, strengthening promotional activities for physical activity participation of the elderly were needed.